Clinical effectiveness of ion-releasing restorations compared to composite restorations in pediatric dental treatments: a systematic review and meta-analysis - Arbildo-Vega, Heber Isac; Cruzado-Oliva, Fredy Hugo; Vásquez-Rodrigo, Hernán; Coronel-Zubiate, Franz Tito; Alarco-La Rosa, Luis Felipe; Alarco-Jurado, Luisfelipe Carlos; Zarate-Chavarry, Stefanny Lisset (Frontiers in Dental Medicine, 2025)
BackgroundThe choice of restorative material in pediatric dentistry is clinically relevant for ensuring long-term tooth preservation and reducing recurrent caries. This systematic review and meta-analysis compared the clinical effectiveness of ion-releasing restorations (IRR) and composite resin (CR) in children's dental treatments.MethodsRandomized clinical trials with ≥1-year follow-up were identified through comprehensive searches in PubMed, Cochrane Library, Scielo, Scopus, Web of Science, and Google Scholar up to January 2024. Studies reporting clinical outcomes of IRR vs. CR were analyzed. Risk of bias was assessed using RoB2.0, and evidence certainty with GRADE.ResultsOf 1,109 records screened, nine trials were included. Pooled analyzes showed no statistically significant differences between IRR and CR regarding secondary caries, marginal adaptation, or restoration survival (p > 0.05). Both materials demonstrated satisfactory longevity and clinical behavior.ConclusionsWithin the limitations of available evidence, ion-releasing and composite restorations provide comparable clinical performance in pediatric dentistry. The findings support the use of IRR as a reliable alternative for child patients, offering bioactive benefits while maintaining similar restorative success to composites.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024524163, PROSPERO CRD42024524163.